Neuropsychological and psychiatric differences between Alzheimer's disease and Parkinson's disease with dementia. Issue 4 (October 1996) - Starkstein, S E; Sabe, L; Petracca, G; Chemerinski, E; Kuzis, G; Merello, M; Leiguarda, R
Abstract : OBJECTIVE: To examine neuropsychological and neuropsychiatric differences between patients with probable Alzheimer's disease and patients with Parkinson's disease and dementia. METHODS: Thirty three patients with probable Alzheimer's disease and 33 patients with Parkinson's disease and dementia were matched for age, sex, and mini mental state examination scores and given a battery of neuropsychological and neuropsychiatric tests. RESULTS: Patients with Parkinson's disease with dementia had a significantly higher prevalence of major depression than patients with Alzheimer's disease; patients with Alzheimer's disease showed more severe anosognosia and disinhibition than patients with Parkinson's disease. Whereas no significant between group differences were found on tests of memory and language, demented patients with Parkinson's disease had a significantly greater impairment on a test of visual reasoning than patients with Alzheimer's disease. CONCLUSION: There were significant psychiatric differences between patients with Alzheimer's disease and demented patients with Parkinson's disease, but neuropsychological differences were restricted to a single cognitive domain.